Rare bird documentation form for Greater Scaup at Lock 14, 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Rare bird documentation form for Greater Scaup at Lock 14 in Scott County, IA on January 2, 1981. Epson - sheet feed